Influence of supplementation of the culture medium on in vitro development of Jatropha curcas - Figueiredo, Nádia Pita [UNESP]; Corrêa, Aretha Arcenio Pimentel [UNESP]; De Moraes, Amanda Carolina Prado [UNESP]; Vianna, Viviane Formice [UNESP]; Di Mauro, Antônio Orlando [UNESP]; Unêda-Trevisoli, Sandra Helena [UNESP] (UNESP - Universidade Estadual Paulista, 2018)
The Jatropha (Jatropha curcas L.) crop stands out for its socioeconomic potential, being an excellent alternative for biodiesel production. Therefore, this study aimed to standardize and optimize in vitro culture of Jatropha embryos and seeds by means of modifications with the addition of vitamin supplements and gibberellic acid in MS medium. We sought to obtain aseptic explants to be used in tissue culture and genetic transformation for the production of standardized seedlings. Two experiments were carried out on MS medium with sucrose and agar. In the first experiment, vitamin complex was added to the culture medium with embryos, at doses of 0.0; 0.5; 1.0; 2.0; 3.0 and 4.0 mL L-1. The second experiment was carried out with seeds added with various doses of gibberellic acid (0.0; 1.0; 2.0; 4.0; 6.0 and 8.0 mg L-1). The experiments were conducted in a completely randomized design with four replicates. Ten variables were analyzed in a two-week period. The results indicated that the addition of vitamins and gibberellic acid to the culture medium is not essential for germination and initial growth, but they provide important increases in seedling shoot and root development.
Keywords: Gibberellic acid; Jatropha; Micropropagation; Vitamin complex